Foreignization and Domestication Ideology in Cultural Term Translation of Novel Tuesday With Morrie: Category Household Goods and House Surroundings - Nico Harared (Masyarakat Linguistik Indonesia Universitas Andalas, 2018)
The research basically aims at identifying translation ideology in cultural term translation of novel Tuesday with Morrie: material culture written by (Albom, 1997), translated by (Widodo, 2009) into an Indonesian language text. Translation ideology classified into its ideology such as foreignization and domestication by (Venuti, 2004) and its techniques of translation theory composed by (Molina & Hurtado Albir, 2002). The research approach is a translation approach by using Newmark’s perspective. The findings show that thereare 9 material cultures especially house goods and household surroundings on Tuesday with Morrie translated into an Indonesian language text. There are six techniques in the data, namely: adaptation, amplification, establish equivalent amplification-adaptation, pure borrowings, establish equivalent, and equivalent description. The ideology of the translation in cultural term category material culture using in this novel is domestication and foreignization. Translation to TL (Bahasa) in this novel gives a shift in the culturalenvironment of cultural elements category material culture in Indonesia.